Validation of a laser driven plasma X-ray microfocus source for high resolution radiography imaging. (February 2021) - Martín, L.; Benlliure, J.; Cortina-Gil, D.; Haruna, A.; Ruiz, C.
Highlights: We present an ultrafast, microfocus, laser driven X-ray source. The source runs in air using an ultrafast laser with moderate energy and a high repetition rate. The X-ray source uses a target system to refresh the material and keep the focus to achieve stability. The source size is small (10 μ m x 12 μ m) and we use it for high resolution radiography. Using different materials the X-ray spectrum can be changed to fit the application. Abstract: Hard X-ray radiation with high brightness and high fluxes is nowadays available on the fourth generation of synchrotrons and X-FELs, but the large size and complexity of these sources makes its use difficult for widespread applications. New table top X-ray sources driven by ultrashort high power lasers offer a compelling route to expand the availability of hard X-ray sources. They can be used for advanced imaging techniques, due to its small source size and spatial coherence. We present in this paper the validation of a compact laser-driven X-ray microfocus source for high-resolution radiography imaging. This novel device was built at the Laser Laboratory for Acceleration and Applications (L2A2) at the University of Santiago de Compostela. This paper describes the laser-plasma X-ray source with improved stability and characterize some of its properties. We demonstrate the high-contrast and resolution of the images obtained with this source by using masks with well known geometries, and detailed analysis by using the modulation transfer function. Finally, we discuss the properties of this source in comparison to other compact microfocus X-ray sources.